Marketing Strategy For Interactive Education At Mis Nurur Rahman Tamanan - Abdul Mukit (Journal of International Multidisciplinary Research, 2025)
This research uses a qualitative approach with a descriptive qualitative method. This research was conducted at MIs Nurur Rahman Tamanan, located at Jl Kebun Bibit No 02 Tamanan, Tamanan District, Bondowoso Regency. The purpose of this research is to analyze the marketing strategies for interactive education at the school and to identify the factors that support and hinder the implementation of these strategies. To provide an understanding of interactive education marketing strategies, data was obtained through field observations and in-depth analysis. The research results show that product, price, promotion, and people are the main indicators in the interactive education marketing strategy. Through school public relations and appropriate pricing, this strategy aims to create a good image. It was found that people's involvement and promotion are important factors in the success of educational service marketing. Nevertheless, the research also found several obstacles. This includes financial difficulties and a lack of public knowledge about interactive education.